Circulation temporelle chez Béatrice Poncelet : Jeux de rythmes et de voix - Sylvie Dardaillon (Strenae)
Béatrice Poncelet, at the end of a complex textualization process, presents picture books in which the scene setting and the movement between image and encountered voices induce a flexible relationship to the linguistic material. The writing, by nature poetic, confronts here an orality of narrative voices in the literary discourse, and this complex weaving of voice and language to another forces the reader to reconsider his relation to the norm, according to a perspective developed by Henri Meschonnic in which rhythm, bound to the physiological, allows poetry to create another semantic network with and against the usual network of the language (Meschonnic, 1970). The combined reading of what we consider to be polyphonic picture book-poems thus invites a complex weaving together of the literary work, the language, and the interpretation.